Parent-Adolescent Communication About Sexuality in Chinese Families. Issue 3 (2nd July 2016) - Wang, Ningxin
ABSTRACT: Given that young people in China are faced with increased sex-related risks, it is important to understand from a communication perspective, the role of parents as a prominent sexual socialization agent for Chinese adolescents. Semistructured, one-to-one interviews were conducted with Chinese adolescents ( N = 37) about their parents' communication about sex and sexuality. Using a constant comparative method, four categories were identified with respect to Chinese parents' direct/explicit communication about sexuality and in addition, four categories of indirect/implication communication (RQ1). Further, four categories regarding Chinese adolescents' attitudes towards such communication were apparent (RQ2). Overall, Chinese parents attempted to transmit values and expectations about dating and sexual activities indirectly, implicitly, and/or nonverbally. Adolescents in the present study also expressed tendencies to avoid sex-related communication with parents. Some even explicitly stated that avoiding such communication was beneficial. The findings' implications for the role of culture in parent-adolescent communication about sexuality and communication openness are discussed.